Information Source Quality and Use as Correlates of Business Performance of Community Banks in Osun State, Nigeria - Fadehan, O.A; https://ir.unilag.edu.ng/items/15a53e31-b7ef-48e7-b216-3902bd1a03bc/full#:~:text=dc.contributor.author-,Popoola%2C%20S.O,-dc.date.accessioned; Popoola, S.O (Ghana Journal of Development Studies, 2023)
27p.